Depression of Vaccinal Immunity to Marek’s Disease by Infection with Chicken Infectious Anemia Virus - Zhang, Yankun; Cui, Ning; Han, Ni; Wu, Jiayan; Cui, Zhizhong; Su, Shuai (Frontiers in Microbiology, 2017)
Marek's disease (MD) has been occurring with increasing frequency in chickens in recent years. To our knowledge, however, there has been no report of the very virulent plus (vv+) MDV field isolate in China. Studies have shown that dual infection with immunosuppressive viruses such as chicken infectious anemia virus (CIAV) occurs frequently in chickens developing MD. In this study, we performed a designed set of in vivo experiments, which comprised five different groups of chickens, including the group of CVI988/Rispens vaccinated chickens, the groups of CVI988/Rispens vaccinated chickens infected with MDV or CIAV or both viruses (MDV and CIAV), and the group of MDV challenged chickens. The effects of CIAV dual infection on the immunization of commercial MDV vaccine CVI988/Rispens were evaluated. The results show that infection of the SD15 strain of CIAV significantly reduced the weight and antibody titers to avian influenza virus (AIV)/Newcastle disease virus (NDV) inactivated vaccines of chickens immunized with the CVI988/Rispens, and resulted in the atrophy of thymus/bursa and the enlargement of spleen. The CVI988/Rispens vaccination conferred good immune protection for chickens challenged with 2000 PFU of the GX0101 strain of MDV. However, dual infection with SD15 significantly reduced the body weight, antibody titers induced by AIV/NDV inactivated vaccines and protective index of CVI988/Rispens, and resulted in the aggravation of the immunosuppression, mortality and viremia of GX0101 in CVI988/Rispens-immunized/GX0101-challenged chickens. Overall, CIAV infection significantly reduced the protective effects of the CVI988/Rispens vaccine against MDV, implying that concurrent infection with CIAV may be a major contributor in the frequent attacks of MD in China in recent years.